The Speech that Didn’t Fly: Polysemic Readings of Christopher Reeve’s Speech to the 1996 Democratic National Convention - Scherman, Elizabeth (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:none; mso-hyphenate:none; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:#00FF;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Actor Christopher Reeve’s address to the 1996 Democratic National Convention was met with enthusiasm by the mainstream press, while the disability press responded with anger and disdain. This paper conducts a rhetorical analysis of text, context and audience reception in order to explore these different interpretations of Reeve’s speech. The study is framed by the concept of polysemy, and in particular Leah Ceccarelli’s concept of strategic ambiguity and John Fiske’s concept of "gaps and fissures" that allow for different meanings to seep through texts. Reeve’s speech was not perceived by members of the disability community as providing such openings for their voices to be heard. The negative reception of Reeve’s speech was further exacerbated by his lack of credibility with many in that community, his choice of language and metaphor, and even the visual rhetoric of his convention appearance.